High-toughness, antibacterial, self-repairable and high-transmittance flexible sensor material and preparation method thereof
By adding elemental sulfur and nanosilver particles to the flexible sensor material to form a polymer network of polysulfide bonds and hydrogen bonds, the antibacterial and self-healing problems of flexible sensor materials are solved, and the comprehensive performance of high toughness, antibacterial, self-healing and high transmittance is achieved.
Patent Information
- Application Number
- CN202510001890.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-02
AI Technical Summary
Flexible sensors are susceptible to bacterial contamination during use, resulting in reduced performance and shortened service life. The existing materials lack self-repair capabilities, which affects sensitivity.
By adding elemental sulfur and nanosilver particles on the basis of polymerization of polyols and polyisocyanates, a polymer network of polysulfide bonds and hydrogen bonds is formed to enhance the antibacterial and self-healing properties of the material.
The material has high toughness, antibacterial properties, self-healing ability and high transmittance, extends its service life and maintains high sensitivity.
Smart Images

Figure CN119798965A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer materials, and specifically relates to a flexible sensor material with high toughness, antibacterial properties, self-repairability and high transmittance, and a preparation method thereof. Background Art
[0002] With the advent of the intelligent era, flexible and stretchable electronic products have shown great market potential. As the core components of these products, flexible sensors can sensitively detect a variety of stimuli related to specific environments or organisms, and play an important role in motion monitoring, electronic skin, clinical diagnosis and other fields. Its unique flexibility, fit and lightweight characteristics make it an important part of the next generation of electronic technology.
[0003] Flexible sensors are often used in wearable devices, medical devices, and other scenarios that require long-term contact with the skin. However, in these environments, bacteria, sweat, and other microorganisms easily adhere to the surface of the sensor. Long-term accumulation may lead to decreased device performance, signal distortion, and even shortened service life. Especially in medical health monitoring, the part where the sensor contacts the skin is more susceptible to bacterial contamination, which may not only affect the detection accuracy of the device, but also threaten human health. Therefore, using materials with antibacterial functions to prepare flexible sensors is an effective strategy that helps to improve the safety and durability of sensors.
[0004] According to the different detection directions, flexible sensors can be divided into strain, pressure, temperature, humidity, pH sensors, etc. However, these sensors will always have a certain amount of wear during use, resulting in a decrease in sensitivity and shortening their service life. Therefore, it is of great application value to prepare flexible sensor materials that are self-repairing at room temperature and have high sensitivity. Summary of the invention
[0005] In order to solve the deficiencies of antibacterial and self-repairing capabilities of flexible sensors, the present invention provides a flexible sensor material with high toughness, antibacterial, self-repairing and high transmittance and a preparation method thereof. The present invention finds that by adding an appropriate amount of elemental sulfur on the basis of polymerization of polyols and polyisocyanates, polysulfide bonds are introduced into polymer segments by capturing hydrogen on polyurethane, which can enhance the stability of the polymer structure, and the prepared material can still maintain a high sensitivity after long-term use. In addition, the present invention adds nanosilver particles to form a complex with sulfur, thereby being evenly dispersed on the polymer chain. Abundant sulfur and nanosilver particles can improve the antibacterial and conductive properties of the material. The interaction between polysulfide bonds and hydrogen bonds can enable the material to repair mechanical damage within a temperature suitable for the human body. The flexible sensor material of the present invention also has a high transmittance and can be used in the fields of artificial skin, wearable devices, etc.
[0006] In order to achieve the above objectives, the present invention is implemented by the following technical solutions:
[0007] A flexible sensor material with high toughness, antibacterial, self-repairability and high transmittance is prepared with polysulfide polymer as raw material. The formula composition according to mass percentage is: 95-99wt% of polysulfide polymer and 1-5wt% of nanosilver particles.
[0008] The polysulfide polymer is composed of: 10-20 wt% elemental sulfur, 25-50 wt% hydroxyl monomer and 30-60 wt% isocyanate monomer.
[0009] The hydroxyl monomers in the polysulfide polymer are: polytetramethylene glycol PTMG-2000, polyethylene glycol PEG-600, polycaprolactone diol PCLDO-530, and tri(pentaerythritol) TPT.
[0010] The isocyanate monomers in the polysulfide polymer are: pentamethylene diisocyanate PDI and isophorone diisocyanate IPDI.
[0011] The preparation method of the polysulfide polymer is as follows: add hydroxyl monomer, isocyanate monomer and elemental sulfur into a reaction bottle according to mass percentage, add a catalyst, react at 80°C for 12 hours, wash with n-hexane solvent after the reaction is completed until the solvent is clear and transparent, dry the sample, and dry the polysulfide polymer.
[0012] The preparation process of the flexible sensor material with high toughness, antibacterial, self-repairing and high transmittance is as follows:
[0013] A. Place the dried polysulfide polymer and nanosilver particles in a flask according to the mass percentage, mix and stir at 80°C for 8 hours, wash with ethanol solvent until the solvent is clear and transparent, and finally dry in a vacuum oven;
[0014] B. The dried mixture is hot-pressed to obtain a flexible sensor material with high toughness, antibacterial, self-repairability and high transmittance. The hot-pressing temperature is 90-100°C and the hot-pressing time is 3-4 minutes.
[0015] Beneficial technical effects:
[0016] (1) The raw materials elemental sulfur and nano silver particles in the present invention provide the material with strong antibacterial ability, which can prevent the growth of microorganisms during the use of the material and affect its use.
[0017] (2) The large number of SS bonds and hydrogen bonds in the polymer network of the present invention endows the material with the ability to self-repair efficiently at a temperature suitable for the human body.
[0018] (3) The material of the present invention has high optical transmittance and can be used in the fields of wearable devices, artificial skin, etc.
[0019] (4) The material of the present invention has long-lasting durability and still maintains high sensitivity after long-term use.
[0020] (5) The material preparation method of the present invention is simple, the raw material price is low, and the production cycle is short, which greatly reduces the production cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 FTIR spectra of the products of Example 1, Example 2, Example 3 and Example 4.
[0022] Figure 2 This is the XPS curve of the product of Example 1.
[0023] Figure 3 The stress-strain curves of the products obtained in Example 1, Example 2, Comparative Example 1, Example 3 and Example 4 are shown.
[0024] Figure 4 The transmittance curves of the products of Example 1 and Example 2 are compared with those of Example 1, Example 3, Example 4 and Example 5.
[0025] Figure 5 The conductivity curves of the products of Example 1, Example 2, Example 3 and Comparative Example 1 are just formed, and after 1 month, 6 months and 12 months.
[0026] Figure 6 This is the stress-strain curve of Example 3 before and after self-repair at room temperature. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments and drawings. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] 100 g of a polysulfide polymer containing 30 wt% pentamethylene diisocyanate PDI, 60 wt% polytetrahydrofuran PTMG-2000, and 10 wt% sulfur after impurity removal and drying, and 5 g of nanosilver particles were placed in a 250 ml flask, mixed and stirred at 80 ° C for 8 h. After the reaction, the mixture was washed with ethanol solvent until the solvent was clear and transparent, and dried in a vacuum oven for 4 h. The dried mixture was hot-pressed at 90 ° C for 3 min to obtain a flexible sensor material with high toughness, antibacterial, self-repairability, and high transmittance.
[0030] The preparation method of the polysulfide polymer is as follows: hydroxyl monomer, isocyanate monomer and elemental sulfur are added into a reaction bottle according to mass percentage, 0.5wt% of the total amount of monomer as sodium hydroxide (NaOH) catalyst is added, and the mixture is reacted at 80°C for 12h. After the reaction is completed, the mixture is washed with n-hexane solvent until the solvent is clear and transparent, and the sample is dried and stored dry.
[0031] Example 2
[0032] 100 g of a polysulfide polymer containing 28 wt% pentamethylene diisocyanate PDI, 57 wt% polytetrahydrofuran PTMG-2000, and 15 wt% sulfur after impurity removal and drying, and 5 g of nanosilver particles were placed in a 250 ml flask, mixed and stirred at 80 ° C for 8 h. After the reaction, the mixture was washed with ethanol solvent until the solvent was clear and transparent, and dried in a vacuum oven for 4 h. The dried mixture was hot-pressed at 90 ° C for 3 min to obtain a flexible sensor material with high toughness, antibacterial, self-healing, and high transmittance.
[0033] The preparation method of the polysulfide polymer is the same as that of Example 1.
[0034] Comparative Example 1
[0035] 100 g of a polymer containing 35 wt% pentamethylene diisocyanate PDI and 65 wt% polytetrahydrofuran PTMG-2000 after impurity removal and drying was placed in a 250 ml flask, mixed and stirred at 80° C. for 8 h. After the reaction was completed, it was washed with ethanol solvent until the solvent was clear and transparent, and dried in a vacuum oven for 4 h. The dried mixture was hot-pressed at 90° C. for 3 min to obtain a flexible sensor material.
[0036] The preparation method of the polymer is the same as that of Example 1.
[0037] Example 3
[0038] 100 g of a polysulfide polymer containing 25 wt% isophorone diisocyanate IPDI, 55 wt% polytetrahydrofuran PTMG-2000 and 20 wt% sulfur after impurity removal and drying, and 5 g of nanosilver particles were placed in a 250 ml flask, mixed and stirred at 80 ° C for 8 h. After the reaction, the mixture was washed with ethanol solvent until the solvent was clear and transparent, and dried in a vacuum oven for 4 h. The dried mixture was hot-pressed at 100 ° C for 4 min to obtain a flexible sensor material with high toughness, antibacterial, self-healing and high transmittance.
[0039] The preparation method of the polysulfide polymer is the same as that of Example 1.
[0040] Comparative Example 2
[0041] 100 g of a polysulfide polymer containing 25 wt% isophorone diisocyanate IPDI, 55 wt% polytetrahydrofuran PTMG-2000 and 20 wt% sulfur after impurity removal and drying was placed in a 250 ml flask, mixed and stirred at 80 ° C for 8 h. After the reaction, it was washed with ethanol solvent until the solvent was clear and transparent, and dried in a vacuum oven for 4 h. The dried mixture was hot-pressed at 100 ° C for 4 min to obtain a flexible sensor material.
[0042] The preparation method of the polysulfide polymer is the same as that of Example 1.
[0043] Example 4
[0044] 100 g of a polysulfide polymer containing 35 wt% isophorone diisocyanate IPDI, 45 wt% polytetrahydrofuran PTMG-2000 and 20 wt% sulfur after impurity removal and drying, and 5 g of nanosilver particles were placed in a 250 ml flask, mixed and stirred at 80 ° C for 8 h. After the reaction, the mixture was washed with ethanol solvent until the solvent was clear and transparent, and dried in a vacuum oven for 4 h. The dried mixture was hot-pressed at 100 ° C for 4 min to obtain a flexible sensor material with high toughness, antibacterial, self-healing and high transmittance.
[0045] The preparation method of the polysulfide polymer is the same as that of Example 1.
[0046] Comparative Example 3
[0047] 100 g of a polymer containing 40 wt% isophorone diisocyanate IPDI and 60 wt% polytetrahydrofuran PTMG-2000 after impurity removal and drying, and 5 g of nanosilver particles were placed in a 250 ml flask, mixed and stirred at 80° C. for 8 h. After the reaction, the mixture was washed with ethanol solvent until the solvent was clear and transparent, and dried in a vacuum oven for 4 h. The dried mixture was hot-pressed at 100° C. for 4 min to obtain a flexible sensor material.
[0048] The preparation method of the polymer is the same as that of Example 1.
[0049] Example 5
[0050] 100 g of a polysulfide polymer containing 48 wt% isophorone diisocyanate IPDI, 32 wt% polyethylene glycol PEG-600, and 20 wt% sulfur after impurity removal and drying, and 5 g of nanosilver particles were placed in a 250 ml flask, mixed and stirred at 80 ° C for 8 h. After the reaction, the mixture was washed with ethanol solvent until the solvent was clear and transparent, and dried in a vacuum oven for 4 h. The dried mixture was hot-pressed at 100 ° C for 4 min to obtain a flexible sensor material with high toughness, antibacterial, self-healing, and high transmittance.
[0051] The preparation method of the polysulfide polymer is the same as that of Example 1.
[0052] Example 6
[0053] 100 g of a polysulfide polymer containing 50 wt% isophorone diisocyanate IPDI, 30 wt% polycaprolactone diol PCLDO-530, and 20 wt% sulfur after impurity removal and drying, and 5 g of nanosilver particles were placed in a 250 ml flask, mixed and stirred at 80 ° C for 8 h. After the reaction, it was washed with ethanol solvent until the solvent was clear and transparent, and dried in a vacuum oven for 4 h. The dried mixture was hot-pressed at 100 ° C for 4 min to obtain a flexible sensor material with high toughness, antibacterial, self-healing, and high transmittance.
[0054] The preparation method of the polysulfide polymer is the same as that of Example 1.
[0055] Example 7
[0056] 100 g of a polysulfide polymer containing 35 wt% isophorone diisocyanate IPDI, 45 wt% tri(pentaerythritol) TPT, and 20 wt% sulfur after impurity removal and drying, and 5 g of nanosilver particles were placed in a 250 ml flask, mixed and stirred at 80 ° C for 8 h. After the reaction, it was washed with ethanol solvent until the solvent was clear and transparent, and dried in a vacuum oven for 4 h. The dried mixture was hot-pressed at 100 ° C for 4 min to obtain a flexible sensor material with high toughness, antibacterial, self-healing, and high transmittance.
[0057] The preparation method of the polysulfide polymer is the same as that of Example 1.
[0058] Example 8
[0059] 100 g of a polysulfide polymer containing 25 wt% isophorone diisocyanate IPDI, 55 wt% polytetrahydrofuran PTMG-2000 and 20 wt% sulfur after impurity removal and drying, and 2.5 g of nanosilver particles were placed in a 250 ml flask, mixed and stirred at 80 ° C for 8 h. After the reaction, it was washed with ethanol solvent until the solvent was clear and transparent, and dried in a vacuum oven for 4 h. The dried mixture was hot-pressed at 100 ° C for 4 min to obtain a flexible sensor material with high toughness, antibacterial, self-healing and high transmittance.
[0060] The preparation method of the polysulfide polymer is the same as that of Example 1.
[0061] Performance test: tensile properties (GB / T 1040.1-2006) were tested at 25°C. The data are shown in Table 1.
[0062] Table 1 Tensile properties and self-healing efficiency of the flexible sensor of the embodiment
[0063]
[0064]
[0065] Note: Mechanical properties test: Three groups of control experiments were established in the test example.
[0066] As can be seen from Table 1, the flexible sensor material synthesized by the present invention has high toughness and can meet the basic requirements for the use of flexible sensors. The flexible sensor material prepared by the present invention can repair mechanical damage within 30 minutes at 35°C and still has good mechanical properties. In addition, the material can adjust its performance by changing the monomer feed and monomer type, and it also has a wide range of adaptability for fixed materials with special requirements.
[0067] The antibacterial properties of the flexible sensor material with high toughness, antibacterial, self-repairing and high transmittance are shown in Table 2. According to the GB / T4789.2-2010 test standard, it can be seen that the flexible sensor material has excellent antibacterial properties.
[0068] Table 2 Antibacterial performance of the flexible sensor of the embodiment
[0069]
[0070] The present invention prepares a flexible sensor material that is plastic at a temperature suitable for the human body, highly antibacterial, highly tough, and highly transparent. The rich sulfur content in the material provides excellent antibacterial properties, preventing the material from increasing the risk of human infection due to bacterial growth. At the same time, the material has high transparency, so it can be used in artificial skin, wearable devices and other fields.
[0071] The conductivity of flexible sensor materials with high toughness, antibacterial, self-repairing and high transmittance is shown in Table 3
[0072] Table 3 Conductivity of the flexible sensor of the embodiment
[0073]
[0074] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A flexible sensor material with high toughness, antibacterial, self-repairing and high transmittance, characterized in that: The flexible sensor material comprises, in terms of mass percentage, 95-99 wt % of polysulfide polymer and 1-5 wt % of nano silver particles.
2. The high-toughness, antibacterial, self-repairable, high-transmittance flexible sensor material according to claim 1, characterized in that: The polysulfide polymer is composed of 10-20 wt % of elemental sulfur, 25-50 wt % of hydroxyl monomers, and 30-60 wt % of isocyanate monomers in terms of mass percentage.
3. The high-toughness, antibacterial, self-repairable, high-transmittance flexible sensor material according to claim 2, characterized in that: The hydroxy monomers are: polytetramethylene glycol PTMG-2000, polyethylene glycol PEG-600, polycaprolactone glycol PCLDO-530, and tri(pentaerythritol) TPT.
4. The high-toughness, antibacterial, self-repairable, high-transmittance flexible sensor material according to claim 2, characterized in that: The isocyanate monomers are: pentamethylene diisocyanate PDI and isophorone diisocyanate IPDI.
5. The high-toughness, antibacterial, self-repairable, high-transmittance flexible sensor material according to claim 1, characterized in that: The preparation method of the polysulfide polymer comprises: adding a hydroxyl monomer, an isocyanate monomer and elemental sulfur into a reaction bottle according to mass percentage, adding a catalyst for reaction, washing until the solvent is clear and transparent after the reaction is completed, and drying the polysulfide polymer.
6. A method for preparing a flexible sensor material with high toughness, antibacterial, self-repairing and high transmittance according to claim 1, characterized in that: The preparation method steps are as follows: A. Place the dried polysulfide polymer and nanosilver particles in a flask according to the mass percentage, mix and stir at 80°C for 8 hours, wash with ethanol until the solvent is clear and transparent, and finally dry in a vacuum oven; B. The dried mixture is hot-pressed to obtain a flexible sensor material with high toughness, antibacterial properties, self-healing properties, and high transmittance.
7. The method for preparing a flexible sensor material with high toughness, antibacterial, self-repairability and high transmittance according to claim 6, characterized in that: The hot pressing temperature in step B is 90-100° C., and the hot pressing time is 3-4 minutes.
8. An application of the flexible sensor material with high toughness, antibacterial, self-repairing and high transmittance according to claim 1, characterized in that: The flexible sensor material is used in the fields of artificial skin and wearable devices.
Citation Information
Patent Citations
Sunlight self-repairing transparent flexible strain sensing composite material, preparation method and applications thereof
CN109265643A
Lipoic acid-nanosilver self-repairing material, and preparation method and application thereof
CN110655651A
Passive capacitance pen point, passive capacitance pen and pen point preparation method
CN111171572A
A polyurethane base lens
CN1129811A
Self-healing material and method for the preparation thereof
EP2597110A1